Dynamics of the nitrogen and phosphorous content in the Rybinsk Reservoir over the many-year period - Irina E. Stepanova (Водное хозяйство России: проблемы, технологии, управление)
Annual dynamics of the biogenic elements content enables to assess the degree of the water bodies’ trophic state and the scale of their anthropogenic euthrophication. We have researched content of all biogenic elements’ forms in the Rybinsk Reservoir in 1993–2018 both in seasonal and temporal aspects. Over the past decades we have registered the trend to increase of phosphates and total phosphorous concentration in the water body. We estimated the reservoir status as mesa/trophic.